Systematic Literature Review: Analisis Dampak Digitalisasi dalam Industri Jasa terhadap Efisiensi dan Layanan Pelanggan - Meivira Dinda Maulidiya Rizqi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Digitalization has become a strategic factor in the transformation of the service industry, increasing operational efficiency and also the quality of customer service. This study aims to conduct an in-depth analysis of the impact of implementing digital technology on two main factors of performance in the service sector, namely business process efficiency and customer satisfaction. The methodology used is the Systematic Literature Review (SLR), by evaluating ten relevant scientific articles published in the last five years. The findings of the analysis indicate that digitalization has a positive impact on accelerating the service process, reducing manual work, and enabling direct data-based decision making. On the other hand, digital technologies such as artificial intelligence, big data analysis, and online service platforms have been shown to increase response speed and personalization in services, which in turn strengthens customer loyalty. However, the success of digital change is greatly influenced by organizational readiness, especially regarding infrastructure, digital literacy capabilities, and business model adjustments. Thus, digitalization in the service industry is not just a technological innovation, but also a managerial change that requires a strategic and comprehensive approach.